(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
The Netherlands faces enormous (re)building challenges. One million new homes need to be built and a multitude of buildings need to be made more sustainable. This requires well-trained and motivated professionals. Small and medium-sized enterprises (SMEs) in the construction and infrastructure sector are also responsible for this. However, SMEs. in particular , are facing growing personnel shortages and a rapidly ageing workforce. To address this dilemma, organizations emphasize the need for smart solutions that provide up-to-date, comprehensive, and reliable insights into the skills available within their workforce. In addition, there is a growing need for professional support to deploy skilled workers effectively, maintain their long-term employability, and provide appropriate and effective guidance throughout this process. This session focused on the results of a project, in which the authors worked with 10 enterprises in construction to experiment with the ’digital skills passport for professionals (DSP)’. The DSP gives employees and companies an up-to-date and complete insight into their own ’skills stock’ and its development. We used this insight to help SMEs offer their (future) employees concrete tools to make their employability more sustainable. Described in the session was intense work with a broad consortium of vocational colleges, universities of applied sciences, social partners, SMEs and knowledge institutions to make the research results usable during the project for (construction) companies themselves and for intermediate and higher vocational education. More specifically, the authors compared the effects of working with the Digital Skills Passport (DSP) and receiving guidance with situations where these elements are absent. The authors discussed how DSP’s guidance and encouragement of learning and development in the workplace lays the foundation for strategic employability and targeted growth. Cooperation between employee, employer, and trainer—the learning triangle—creates shared ownership of professional development. In this way, the session offered insights into the applicability and usability of the DSP in various organizational contexts and discussed mechanisms such as motivation, resistance, and autonomy as keys to sustainable development. Keywords: digital skills passport, building challenges in Netherlands, sustainable development learning triangle